What impact does the adoption of drought-tolerant maize for Africa have on the yield and poverty status of farmers in the arid region of Nigeria? - Obayelu, Oluwakemi Adeola; Fakolujo, Olutomi Marian; Awotide, Bola Amoke (Journal of Agricultural Sciences (Belgrade), 2019)
Maize production in Nigeria was not enough enough to meet the needs of people due to drought, low productivity and lack of access to improved varieties by farmers. Increased agricultural yield is a potential means for increasing household income tends to lower the poverty status of small holders. This study assessed the impact of Drought Tolerant Maize for Africa (DTMA) on yield and poverty status of farmers in the Northwestern region of Nigeria. The study used data from the Adoption of DTMA survey by the International Institute of Tropical Agriculture (IITA), Ibadan, for Northwest Nigeria has 293 respondents (90 adopters and 203 non-adopters of DTMA). Data were analyzed using descriptive statistics, binary regression and propensity score marching methods. Results showed that small-holder farmers were more likely to adopt DTMA than larger farms. Adopters had an increase in DTMA yield of 9,262.77kg / ha while counterfactual non-adopters had an increase of 3807.74kg / ha. Adoption of DTMA reduced the probability of being poor by 60% for the treatment group while the incidence of poverty decreased by 35% among non-adopters. The general conclusion is that while the DTMA adoption program had a positive treatment effect on yield of households